Innovation in design and engineering: the refill_h2o - Curralo, Ana Filomena (2025)
This article explores the design journey behind a water dispensing system composed of a reusable water bottle and a smart refill station interconnected through the Internet of Things (IoT) and Information and Communication Technologies (ICT). The methodology embraced Design Thinking and Participatory Design, seeking insights and feedback from the intended users throughout the Smartbottle ecosystem’s development phases. These insights substantiated the eco-friendly product specifications and design requisites, culminating in a solution tailored to a specific community. The primary aim of this system is to gradually phase out the use of single-use plastic water bottles within the premises of Polytechnic Institute of Viana do Castelo, an institution catering to around 6000 students and staff members. A survey conducted revealed a preference for recycled plastic as the material of choice, while the design of the bottle took on a marine animal shape. This symbolic choice represents the extensive ecological impact of discarding conventional plastic bottles, emphasizing the global urgency to curtail plastic waste, pollution, and accumulation.